1988
DOI: 10.1080/00365599.1988.11690417
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Diversion To The Augmented and Valved Rectum an Experimental Study in Dogs

Abstract: A new model for diverting urine to the rectum was tried in dogs. An intussusception valve was constructed at the junction of the sigmoid colon and the rectum allowing passage only in aboral direction. The rectum was augmented by patching it with an opened and folded ileal segment. The ureters were implanted into the rectum by a new anti-reflux method. All three dogs survived the operation. The volume of the augmented rectum increased from 80-150 ml at operation to a maximum of 750 ml six months after the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In two patients, a modification of the technique described by Kock et al [ 5] was used. The same 20 cm of lower rectum and sigmoid were identified, the bowel opened longitudinally and augmented with a patch of ileum, after the ureters had been implanted.…”
Section: Methodsmentioning
confidence: 99%
“…In two patients, a modification of the technique described by Kock et al [ 5] was used. The same 20 cm of lower rectum and sigmoid were identified, the bowel opened longitudinally and augmented with a patch of ileum, after the ureters had been implanted.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2) with anti-reflux nipple (35 males and 14 females) [3] and 1 male without anti-reflux nipple [4], 3 with a ureteroileal rectosigmoidostomy (2 males and 1 female) [5], and 1 male with an ileum augmentation of a rectum bladder [6].…”
mentioning
confidence: 99%
“…The colorectal valve limits the colonic absorptive surface by functionally isolating the rectal reservoir; it prevents the regurgitation of rectal contents to the rest of proximal colon. Moreover, both experimental and clinical studies showed an unimpeded flow of colonic contents distally to the rectal reservoir and through the constructed intussuscepted valve [ 8–10].…”
Section: Discussionmentioning
confidence: 99%
“…These differences probably arose from the reduction in the surface area available for reabsorption when a valve is constructed. Moreover, the valve, being isoperistaltic, caused no impedance in the passage of the colonic fecal contents to the rectal reservoir [ 6–10]. However, it is important to verify that the augmented and valved rectum does not affect intestinal motility and the present study was conducted to address this issue for the colorectal valve.…”
Section: Introductionmentioning
confidence: 99%